2005
DOI: 10.1093/auk/122.3.733
|View full text |Cite
|
Sign up to set email alerts
|

Flight Calls and Their Value for Future Ornithological Studies and Conservation Research

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 69 publications
2
44
0
Order By: Relevance
“…NFC detections are known to be positively related to increasing cloud cover (or decreasing cloud ceiling, which correlated very strongly with cloud cover in this study) or decreasing visibility (reviewed in [35]; see also [47]). Farnsworth [35] suggested that increased calling rates by individuals under conditions of poor visibility may be adaptive for maintaining contact, avoiding collisions, and coordinating migratory behavior, particularly in inexperienced migrants [48]; this hypothesis implies a behavior-modifying influence on calling rates. Its potential pertinence to inexperienced migrants is particularly relevant to this study, as the vast majority of autumnal songbird migrants along the coast are young birds performing their first migration [49]–[53].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…NFC detections are known to be positively related to increasing cloud cover (or decreasing cloud ceiling, which correlated very strongly with cloud cover in this study) or decreasing visibility (reviewed in [35]; see also [47]). Farnsworth [35] suggested that increased calling rates by individuals under conditions of poor visibility may be adaptive for maintaining contact, avoiding collisions, and coordinating migratory behavior, particularly in inexperienced migrants [48]; this hypothesis implies a behavior-modifying influence on calling rates. Its potential pertinence to inexperienced migrants is particularly relevant to this study, as the vast majority of autumnal songbird migrants along the coast are young birds performing their first migration [49]–[53].…”
Section: Discussionsupporting
confidence: 50%
“…However, consistent precipitation also compromises the detectability of NFCs by increasing the background noise (see below). In contrast, light to moderate precipitation may decrease visibility without hindering migration and thus induce increased calling rates [35], [47] or lower flight altitudes [8], thereby increasing detections.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many North American species of birds give distinctive flight calls during nocturnal migration (Evans and O'Brien 2002). Monitoring the flight calls of nocturnally migrating birds can be useful for studying the timing and magnitude of migration, as well as for confirming the presence of individual species (Farnsworth 2005). Recent technological advances in acoustic monitoring, such as increased processor speed, automated detection software, increasing data storage capacities, and a comprehensive identification guide (Evans and O'Brien 2002), permit recording of the vocalizations of passing migrants over entire nights, thus yielding data on species composition, migration timing and routing, and the magnitude of migration traffic.…”
mentioning
confidence: 99%